Monetary, Credit and Banking - Nguyen, Xuan Hai (Khoa Quốc tế, ĐHQGHN, 2020)
This course is designed to provide students with the necessary knowledge and skills in money, credit and banking. The emphasis of this course is on conceptual and theoretical aspects of monetary, credit, banking and financial institutions in general. It allows understanding micro-finances and macro environment of finance. The emphasis on credit and banking for business students is to have acomprehensive overview of the financial system.